2016
DOI: 10.7883/yoken.jjid.2015.061
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and Virologic Studies of an Imported Dengue Case Occurring in 2014 in Okinawa, Japan

Abstract: SUMMARY: After returning from Bali, Indonesia, in February 2014, a 72-year-old man was hospitalized in Okinawa owing to a high fever and rash. Dengue was clinically suspected, and the patient tested positive for IgM against dengue using a commercial kit. Serologically, the patient showed secondary seroreactivity. Significant increases in neutralization titers (N-titers) against all 4 serotypes of dengue virus (DENV) and Japanese encephalitis virus (JEV) strains were recognized in convalescent-phase sera compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…DENV‐1 Genotype I was first isolated in Indonesia in 2006 and quickly became the most frequently isolated DENVs in Indonesia. Genotype I viruses have been sampled over a wide geographical range, not only in regions of Java Island, but also in Bali, Jambi, Makassar, and Manado . Since its first detection in Indonesia, Genotype I has frequently been reported to cocirculate with Genotype IV in several regions in the country …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DENV‐1 Genotype I was first isolated in Indonesia in 2006 and quickly became the most frequently isolated DENVs in Indonesia. Genotype I viruses have been sampled over a wide geographical range, not only in regions of Java Island, but also in Bali, Jambi, Makassar, and Manado . Since its first detection in Indonesia, Genotype I has frequently been reported to cocirculate with Genotype IV in several regions in the country …”
Section: Resultsmentioning
confidence: 99%
“…Although introduction of this genotype occurred relative recently, the viruses of this genotype were the most frequently isolated virus within DENV‐1 in Indonesia. This genotype has been isolated in almost all Indonesian main islands, suggesting that this virus may be more efficiently transmitted and is better at adapting to new ecological niches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis revealed that all of the 10 DENV -1 isolates were grouped into Genotype I (Fig 1). The isolates were closely related to Bali strains from imported cases to Australia in 2010 [9] and 2011 [8] and Japan [10] and strains from other cities in Indonesia i.e. Makassar [18] and Surabaya [29].…”
Section: Discussionmentioning
confidence: 99%
“…This transmission created substantial DENV diversity and serve as a hub for dengue transmission and mixing in Bali [8]. Most of the reports of dengue in travelers returning from Indonesia have implicated Bali as the source of importation [810]. All four DENV serotypes were detected from travelers entering Western Australia between 2010–2012, mostly from Bali [8].…”
Section: Introductionmentioning
confidence: 99%